2021
DOI: 10.54386/jam.v23i1.90
|View full text |Cite
|
Sign up to set email alerts
|

Crop-weather based relation and severity prediction of aerial blight incited by Rhizoctonia solani Kuhn in soybean

Abstract: Crop-weather based relation and other aspects of aerial blight incited by Rhizoctoniasolani Kuhn were investigated on two mega varieties (JS 335 and JS 97-52, now susceptible) under central Indian conditions during 2017, 2018 and 2019. It was found that aerial severity and sclerotial formation on affected leaves were varied significantly in all three season, and progress of disease was rapid between 63–84 days old crop {full pod (R4) to maturity initiation (R7) stage}.Increasing crop age was also signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…From the models, it can be inferred that weather parameters like, maximum and minimum temperature and evening relative humidity played crucial role in disease development during three years of investigation, and the regression equation formulated on the basis of these parameters appears to be the best fit. Amrate et al, (2021) also found best model with three significant weather variables (Mean Relative Humidity, Rainfall and Minimum temperature) for prediction of Rhizoctonia aerial blight of soybean.…”
Section: Disease Prediction Modelsmentioning
confidence: 85%
“…From the models, it can be inferred that weather parameters like, maximum and minimum temperature and evening relative humidity played crucial role in disease development during three years of investigation, and the regression equation formulated on the basis of these parameters appears to be the best fit. Amrate et al, (2021) also found best model with three significant weather variables (Mean Relative Humidity, Rainfall and Minimum temperature) for prediction of Rhizoctonia aerial blight of soybean.…”
Section: Disease Prediction Modelsmentioning
confidence: 85%
“…The findings are per the observations of other researchers in developing prediction models for disease assessment. Amrate et al, (2021) developed a disease forecasting model for the prediction of Rhizoctonia aerial blight of soybean with three significant weather variables (mean relative humidity, rainfall, and minimum temperature). Kulkarni and Raja (2019) studies indicate a negative correlation with temperature and a positive correlation with relative humidity and rainfall on per cent disease index and spore load of mung bean anthracnose.…”
Section: Multiple Regression Modelmentioning
confidence: 99%
“…It is more serious and widespread disease of soybean in the Northern and Central India and Pantnagar is considered as a hotspot for YMD. Understanding of weather factors and their role in disease incidence is a prerequisite for developing disease forewarning system (Amrate et al, 2021). Hence, a detailed investigation was undertaken to study the influence of weather parameters on the incidence of YMD and differential response of the soybean genotypes varying in YMD resistance under varying agro-climatic conditions.…”
mentioning
confidence: 99%